Multifactorial Design of a Supramolecular Peptide Anti-IL-17 Vaccine Toward the Treatment of Psoriasis - Shores, Lucas S.; Kelly, Sean H.; Hainline, Kelly M.; Suwanpradid, Jutamas; MacLeod, Amanda S.; Collier, Joel H. (Frontiers in Immunology, 2020)
Current treatments for chronic immune-mediated diseases such as psoriasis, rheumatoid arthritis, or Crohn’s disease commonly rely on cytokine neutralization using monoclonal antibodies; however, such approaches have drawbacks. Frequent repeated dosing can lead to the formation of anti-drug antibodies and patient compliance issues, and it is difficult to identify a single antibody that is broadly efficacious across diverse patient populations. As an alternative to monoclonal antibody therapy, anti-cytokine immunization is a potential means for long-term therapeutic control of chronic inflammatory diseases. Here we report a supramolecular peptide-based approach for raising antibodies against IL-17 and demonstrate its efficacy in a murine model of psoriasis. B-cell epitopes from IL-17 were co-assembled with the universal T-cell epitope PADRE using the Q11 self-assembling peptide nanofiber system. These materials, with or without adjuvants, raised antibody responses against IL-17. Exploiting the modularity of the system, multifactorial experimental designs were used to select formulations maximizing titer and avidity. In a mouse model of psoriasis induced by imiquimod, unadjuvanted nanofibers had therapeutic efficacy, which could be enhanced with alum adjuvant but reversed with CpG adjuvant. Measurements of antibody subclass induced by adjuvanted and unadjuvanted formulations revealed strong correlations between therapeutic efficacy and titers of IgG1 (improved efficacy) or IgG2b (worsened efficacy). These findings have important implications for the development of anti-cytokine active immunotherapies and suggest that immune phenotype is an important metric for eliciting therapeutic anti-cytokine antibody responses.